Chitosan/Polycyclodextrin (CHT/PCD)-Based Sponges Delivering VEGF to Enhance Angiogenesis for Bone Regeneration - Carla Palomino-Durand; Marco Lopez; Pierre Marchandise; Bernard Martel; Nicolas Blanchemain; Feng Chai (MDPI AG, 2020)
Vascularization is one of the main challenges in bone tissue engineering (BTE). In this study, vascular endothelial growth factor (VEGF), known for its angiogenic effect, was delivered by our developed sponge, derived from a polyelectrolyte complexes hydrogel between chitosan (CHT) and anionic cyclodextrin polymer (PCD). This sponge, as a scaffold for growth factor delivery, was formed by freeze-drying a homogeneous CHT/PCD hydrogel, and thereafter stabilized by a thermal treatment. Microstructure, water-uptake, biodegradation, mechanical properties, and cytocompatibility of sponges were assessed. VEGF-delivery following incubation in medium was then evaluated by monitoring the VEGF-release profile and its bioactivity. CHT/PCD sponge showed a porous (open porosity of 87.5%) interconnected microstructure with pores of different sizes (an average pore size of 153 μm), a slow biodegradation (12% till 21 days), a high water-uptake capacity (~600% in 2 h), an elastic property under compression (elastic modulus of compression 256 ± 4 kPa), and a good cytocompatibility in contact with osteoblast and endothelial cells. The kinetic release of VEGF was found to exert a pro-proliferation and a pro-migration effect on endothelial cells, which are two important processes during scaffold vascularization. Hence, CHT/PCD sponges were promising vehicles for the delivery of growth factors in BTE.